Sharia Risk of Government-Owned Islamic Rural Banks during COVID-19 in Indonesia - Riza Zahrotun Nisa; Yunieta Anny Nainggolean; Taufik Faturohman (University of Merdeka Malang, 2021)
This study examines the effect of government ownership on the sharia risk of Islamic rural banks using all publicly available data of 156 BPRSs from 23 provinces in Indonesia. This research uses a quantitative method with secondary data obtained from the Financial Services Authority (OJK). Regressions using panel data regressions are employed to analyze the relationship between government ownership and sharia risk. Non-halal income is employed to measure the sharia risk between 2019 Q4 and 2020 Q3, representing the timeline before and during COVID-19. In all models and periods, the results found a significant positive effect of government ownership variables on non-halal income. However, the degree decreases during the COVID-19 pandemic. It reveals that government-owned Islamic rural banks are found to have lower non-halal income during the pandemic. We also find that more significant firms with higher leverage tend to have higher non-halal income. This study is expected to contribute to the still thin literature on sharia risk, especially in the context of Islamic rural banks in Indonesia. Results will have implications to the regulator to assure the sharia compliance of the Islamic finance industry. This is essential to gain trust from the Islamic society, which is concerned about the observance of Islamic banks.JEL: G21